Stress Relaxation and Viscoelastic Creep of Polymer Composites: A Critical Review of Models, Methods, and Mechanisms - Jiang, Haozhe (Scientific Journal of Technology, 2026)
This review provides a comprehensive and critical assessment of the literature on stress relaxation and viscoelastic creep in polymer composites, covering constitutive modeling, relaxation-creep interconversion, energy dissipation, time-dependent damage, and temperature effects. Three major constitutive approaches are compared and evaluated: the Prony series, the Standard Linear Solid model with finite loading rate correction, and fractional-order viscoelastic models. For interconversion, the Boltzmann convolution integral, direct SLS prediction formulas, and the engineering J 1/E approximation are critically assessed. A time-dependent damage framework D(t) extended from Weibull fatigue damage is discussed. Key gaps in the literature are identified, and future research directions are proposed.